Synthesis and Characterization of ZrO2-Pillared Bentonites - Suseno, Ahmad; Wijaya, Karna; Trisunaryanti, Wega; Shidiq, Mohamad (Asian Journal of Chemistry, 2015)
Bentonite is a clay mineral that has layered structure, porous and having potential as a catalyst as well as an adsorbent. Pillarization process against bentonite aims to increase the surface area, pore volume, thermal stability and catalytic active sites of pillar metal oxide. Pillarization mechanism stages begin with pillar ion exchange in interlayer structure ions with the formation of oxide ions into the metal oxide through calcination. Characterization towards bentonite pillared synthesis result was performed using AAS, XRD, TEM and analysis of N2 adsorption/ desorption. The analysis showed that the surface area and pore volume of ZrO2 pillared bentonite increased from 52.830 m2/g and 0.152 cc/g into 269.165 m2/g and 0.204 cc/g. The XRD and TEM analysis also showed that the presence of metal oxide ZrO2 was able to increase the basal spacing of 1.38 to 1.89 nm and raised no damage to the structure of bentonite.